Ecologies of evidence in a mysterious epidemic (Medicine Anthropology Theory, 2016)
An epidemic in a Venezuelan rainforest in 2007-2008 killed 38 children and young adults, puzzling clinicians, epidemiologists, and healers alike for over a year. This essay traces the way each contribution to knowledge production formed part of a larger ecology of evidence. Focusing on how the parents' knowledge was exploited and denigrated by clinicians, epidemiologists, and healers alike points to the health/communicative inequities—grossly unequal distributions of access to the production and circulation of evidence—that structured ecologies of evidence in ways that thwarted diagnosis. Recruiting a nurse, a healer, a physician, and an anthropologist, two indigenous leaders launched an investigation that juxtaposed parents' narratives, vernacular healing, epidemiology, and clinical medicine, resulting in a clinical diagnosis of bat-transmitted rabies. This case suggests that perspectives in global health will fail to become fully critical unless they attend to health/communicative inequities, how they structure ecologies of evidence, and strategies for transforming them.